Adaptor mediated activation of the Hsp100/ Clp protein ClpC controls general and regulatory proteolysis in Bacillus subtilis - Turgay, Kursad (Henry Stewart Talks, 2007)
Adaptor protein activation of ClpCP mediated proteolysis in B. subtilis Hsp100/Clp proteins and proteolysis, ClpCP of B. subtilis in competence development and protein quality control, Adaptor protein (MecA) mediated activation of ClpCP, McsB a new regulated adaptor protein, Adaptor protein network for ClpCP of B. subtilis
Archived at 2021/02/25